Acceptability and feasibility of plasma phosphorylated‐tau181 in two memory services. (7th March 2023) - Hazan, Jemma; Hall, Simon; Pemberton, Alex; Sherriffs, Ian; Joels, Suzanne; Heslegrave, Amanda; Veleva, Elena; Ghauri, Mamoona; Laban, Rhiannon; Abel, Emily; Zetterberg, Henrik; Fox, Nick C.; et al.
Abstract: Background: Plasma phosphorylated‐tau181 (p‐tau181) represents a novel blood‐based biomarker of Alzheimer's disease pathology. We explored clinicians' experience of the utility of plasma p‐tau181 in Camden and Islington Memory Services. Methods: Patients were identified by their clinician as appropriate for p‐tau181. Their p‐tau181 result was plotted on a reference range graph provided to clinicians. This was discussed with the patient at diagnostic feedback appointment. Results: Twenty‐nine participants' plasma p‐tau181 samples were included (mean age 74 SD 8.5, 65% female). Nine clinicians participated in the study. Eighty‐six percent of clinicians found the p‐tau181 result to be helpful and in 93% of cases it was clearly understandable. The p‐tau181 result was useful in making the diagnosis in 44% of cases. Conclusions: Plasma p‐tau181 is a feasible test for use in memory services and acceptable to clinicians. Clinician feedback on utility in dementia diagnoses was mixed. Further work is required to provide education and training in understanding and interpreting ambiguity in biomarker results. Key points: Results from this study show that plasma phosphorylated‐tau181 (p‐tau181) is feasible to incorporate in the diagnostic assessment of patients in a memory service and acceptable to clinicians. Clinicians require education and training in understanding and interpreting ambiguity in biomarker results. Further work is needed to establish the clinical utility of such a blood biomarker in UK Memory Services and to investigate the impact of p‐tau181 results for Alzheimer's disease diagnoses, clinicians' diagnostic confidence and patient management.